The Double Tidal Disruption Event AT 2022dbl Implies that at Least Some “Standard” Optical Tidal Disruption Events Are Partial Disruptions - Lydia Makrygianni; Iair Arcavi; Megan Newsome; Ananya Bandopadhyay; Eric R. Coughlin; Itai Linial; Brenna Mockler; Eliot Quataert; Chris Nixon; Benjamin Godson; Miika Pursiainen; Giorgos Leloudas; et al. (The Astrophysical Journal Letters)
Flares produced following the tidal disruption of stars by supermassive black holes can reveal the properties of the otherwise dormant majority of black holes and the physics of accretion. In the past decade, a class of optical-ultraviolet tidal disruption flares has been discovered whose emission properties do not match theoretical predictions. This has led to extensive efforts to model the dynamics and emission mechanisms of optical-ultraviolet tidal disruptions in order to establish them as probes of supermassive black holes. Here we present the optical-ultraviolet tidal disruption event AT 2022dbl, which showed a nearly identical repetition 700 days after the first flare. Ruling out gravitational lensing and two chance unrelated disruptions, we conclude that at least the first flare represents the partial disruption of a star, possibly captured through the Hills mechanism. Since both flares are typical of the optical-ultraviolet class of tidal disruptions in terms of their radiated energy, temperature, luminosity, and spectral features, it follows that either the entire class are partial rather than full stellar disruptions, contrary to the prevalent assumption, or some members of the class are partial disruptions, having nearly the same observational characteristics as full disruptions. Whichever option is true, these findings could require revised models for the emission mechanisms of optical-ultraviolet tidal disruption flares and a reassessment of their expected rates.